2012
DOI: 10.1021/je3005694
|View full text |Cite
|
Sign up to set email alerts
|

Adsorptive Water Removal from Primary Alcohols and Acetic Acid Esters in the ppm-Region

Abstract: Dry organic solvents are important for many industrial sectors. Adsorptive water removal is one technique to obtain highly pure solvents. However, in-depth knowledge of the parameters influencing adsorption behavior is still fragmentary. This paper presents a systematic investigation of water adsorption from alcohols (C1 to C6) and acetic acid esters (methyl acetate to n-butyl acetate) of different chain lengths. Zeolites of types 3A and 4A are used as adsorbents. The impact of size exclusion on adsorption pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 12 publications
1
5
0
Order By: Relevance
“…These results are in accordance with the findings of adsorptive drying of higher alcohols (>C4) and esters. 7 , 8 According to Basmadjian, 2 if solvent molecules cannot penetrate the pores of the molecular sieves, the water adsorption isotherm is independent of the solvent and is the same as a pure water vapor isotherm.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These results are in accordance with the findings of adsorptive drying of higher alcohols (>C4) and esters. 7 , 8 According to Basmadjian, 2 if solvent molecules cannot penetrate the pores of the molecular sieves, the water adsorption isotherm is independent of the solvent and is the same as a pure water vapor isotherm.…”
Section: Resultsmentioning
confidence: 99%
“…Adsorption is one of the possible methods for obtaining ultrapure solvents. 2 Because of their high hygroscopicity, molecular sieves have already demonstrated their adsorption capability for the drying of ethanol, 3 , 4 higher alcohols 5 , 6 and esters, 7 , 8 toluene, 9 and other hydrocarbons 10 and solvents. 11 The general conclusion is that hydrophobic solvents are easier to dry.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They conducted preliminary batch equilibrium experiments in the system (formaldehyde + methanol + water + OME) on zeolite 3A, assuming exclusive water adsorption. However, due to size considerations, the coadsorption of particularly formaldehyde and methanol cannot be excluded. …”
Section: Introductionmentioning
confidence: 99%
“…Recently some researcher reported that bio-based desiccants adsorb water up to 4.5% by weight from alcohol water mixture. They concluded that, uptake capacity of water in vapor form is higher than that of liquid for effective adsorption 17,18 . In this present work the optimization of various parameters like silica gel weight, Hot air temperature and molar ratio for response of energy consumption in a microcontroller based embedded system for esterification of acetic acid and nbutanol is studied.…”
Section: Introductionmentioning
confidence: 99%